Crystallographic and Hirshfeld surface analysis of 10-(4-chlorophenyldiazenyl)-3-(3-chlorophenyl)-1-methyl-3,5a,6,11b-tetrahydro-5H-benzopyrano[4',3'-4,5]pyrano[2,3-c]pyrazole - Gupta, Vivek Kumar; Sharma, Naresh; Sharma, Archna; Teraiya, Shashikant Bhikhubhai; Parmar, Narsidas Jeramdas; Sharma, Deepak (European Journal of Chemistry, 2025)
The title compound, 10-(4-chlorophenyldiazenyl)-3-(3-chlorophenyl)-1-methyl-3,5a,6,11b-tetrahydro-5H-benzopyrano [4',3'-4,5]pyrano[2,3-c]pyrazole, crystallizes in the triclinic crystal system having the space group P-1 with the following unit cell parameters: a = 7.599(2), b = 11.596(3), c = 12.796(3) Å, α = 90.092(5), β = 94.810(5), γ = 90.583(5)°, Z = 2. The crystal structure was solved by direct methods using single-crystal X-ray diffraction data collected at 100 K and refined by full-matrix least-squares procedures to a final R-value of 0.0636 for 2578 observed reflections. All three phenyl rings A, B, and F are planar. The pyrazole ring E is also planar. Rings C and D are in half-chair conformation with asymmetry parameters: ΔC2(C7a-C11a) = 3.02 and ΔC2(C3a-C11c) = 4.02, respectively. Hirshfeld surface is a 3D boundary around a molecule/crystal structure based on electron density. The Hirshfeld surface analysis revealed dominant H···H (31.0%), H···Cl (26%), and H···C (18%) interactions, contributing to crystal stability and packing efficiency. Molecular docking studies further indicated a strong and stable ligand-enzyme interaction, highlighting its potential for small-molecule inhibitor development.